High Values of the Leukocyte Glycemic Index Are Associated with Symptomatic Systemic Atherosclerotic Disease in Young Patients - Coșarcă Mircea Cătălin; Horváth Emőke; Lazăr Nicolae-Alexandru; Carașcă Cosmin; Ráduly Gergő; Constantin Maria; Szanto Ludovic-Alexandru; Bandici Corneliu Bogdan; Bartus Réka; Șincaru Suzana-Vasilica; Mureșan Adrian Vasile (Journal of Cardiovascular Emergencies)
Peripheral artery disease (PAD), traditionally affecting older adults, is increasingly diagnosed in younger patients, highlighting the need for early, non-invasive biomarkers such as the leukocyte glycemic index (LGI) that reflect the inflammatory mechanisms driving atherosclerosis. The aim of this study was to determine whether the LGI can be associated with the presence of symptomatic atherosclerotic disease on patients under 45 years.